Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1186/s12872-020-01388-2
|View full text |Cite
|
Sign up to set email alerts
|

Different adiposity indices and their associations with hypertension among Chinese population from Jiangxi province

Abstract: Background: To date, the best adiposity index that predicts or associates strongly with hypertension remains controversial. Therefore, we aimed to compare the performance of different adiposity indices [BMI (body mass index), WC (waist circumference), WHtR (waist-to-height ratio), ABSI (a body shape index), VAI (visceral adipose index), BFP (body fat percentage)] as associates and potential predictors of risk of hypertension among Chinese population. Methods: A cross-sectional survey was conducted in Jiangxi p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 33 publications
(45 reference statements)
3
19
0
Order By: Relevance
“…Regarding to gender-speci c effect of adiposity indices for hypertension, we found that female were more likely in higher risk of hypertension incidence than male in line with previous studies (25,26). Those results could be explained by the following points.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Regarding to gender-speci c effect of adiposity indices for hypertension, we found that female were more likely in higher risk of hypertension incidence than male in line with previous studies (25,26). Those results could be explained by the following points.…”
Section: Discussionsupporting
confidence: 90%
“…It is con rmed that metabolic health is a transient phenotype. Subgroups of obese individuals with metabolic abnormalities or not may have different risk of cardiovascular disease (CVD) (25,26). On the other hand, metabolically unhealthy individuals are at high risk of CVD irrespective of BMI (27).While the association between obesity and the metabolic status (MS) has been widely studied, it is still proposed merely a dose-response relationship (27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we found that the VFA's advantage in identifying hypertension in women was gradually replaced by BMI with age. The reason for this change might be related to the secretion of free fatty acids and angiotensinogen, and sympathetic nervous system activation [ 35 ], which could slowly decrease the influence of visceral fat. Given the superiority of VFA in identifying females with hypertension, the mechanism of visceral fat's influence on female hypertension is worthy of further study.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, ABSI has received more and more attention. Subsequent studies revealed the relationship between ABSI and arterial stiffness [19], carotid atherosclerosis [20], hypertension [21], metabolic syndrome [22], diabetes and CVD [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%